The Effect of COVID 19 Pandemic on English Proficiency Level in Higher Education - Mohammad Amiruddin; Ukhti Raudhatul Jannah (Journal of English Language Teaching and Linguistics, 2021)
This study is to find out the effect of COVID 19 pandemic on English proficiency .This research is an experimental research using quantitative approach. The students in higher education are as parts of population in this research. A random sampling technique is used to decide the sampling size. The subjects of this study are 36 students. The data are analyzed by paired t test technique.  The result of the study shows sig (p) is significant. It is smaller than 0.05 (it is 0.000). The difference can be considered true. The mean is 59.30 before COVID 19; 49.33 is the mean during COVID 19. It indicates that the students at higher education with before COVID 19 pandemic have better English aptitude than in COVID 19 virus. It implies that the teachers and members of educational society in higher education be supposed to assist out students with the suitable atmosphere to be of assistance students with consequential input in addition to offer students with interface in an attempt to the regularity of experiencing English; additionally, it is suggested that the members of scholar society are being release significant input for the students.